2018
DOI: 10.3390/ijerph15040741
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Indoor Air Quality Problems in Office-Like Environments: Role of Occupational Health Services

Abstract: There is an increasing concern about indoor air quality (IAQ) and its impact on health, comfort, and work-performance in office-like environments and their workers, which account for most of the labor force. The Scientific Committee on Indoor Air Quality and Health of the ICOH (Int. Comm. Occup. Health) has discussed the assessment and management of IAQ problems and proposed a stepwise approach to be conducted by a multidisciplinary team. It is recommended to integrate the building assessment, inspection by wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 46 publications
0
45
0
5
Order By: Relevance
“…These problems should be examined from a wider perspective, and experience of the users of the premises and the psychosocial environment should be considered [20][21][22][23]. It has been suggested that good practices for solving complex or prolonged IAQ problems are well organised and involve long-term multiprofessional cooperation between experts [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…These problems should be examined from a wider perspective, and experience of the users of the premises and the psychosocial environment should be considered [20][21][22][23]. It has been suggested that good practices for solving complex or prolonged IAQ problems are well organised and involve long-term multiprofessional cooperation between experts [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…When indoors, humans are exposed not only to ozone, but also to products of ozone‐initiated chemistry . Some of these products (eg, hydroxyl radicals, hydrogen peroxide, organic peroxides, formaldehyde, dicarbonyls, secondary organic aerosols) potentially contribute to the total mortality associated with long‐term exposure to ozone as evaluated using measured or modeled outdoor ozone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…50 When indoors, humans are exposed not only to ozone, but also to products of ozone-initiated chemistry. 20,23,36,[51][52][53][54][55][56][57][58][59][60][61][62][63][64] Some of these products (eg, hydroxyl radicals, hydrogen peroxide, organic peroxides, formaldehyde, dicarbonyls, secondary organic aerosols) potentially contribute to the total mortality associated with long-term exposure to ozone as evaluated using measured or modeled outdoor ozone concentrations. Indeed, some of the same products generated when ozone is inhaled are generated indoors and subsequently inhaled (albeit at much lower "intake ratios").…”
Section: Exposure To Indoor Ozone and Its Oxidation Productsmentioning
confidence: 99%
“…The practical implication of this study is that supervisors, occupational health practitioners and other authorities should be aware of the importance of fair and supportive treatment when they are resolving suspected or observed IE problems in the workplace. Besides the careful investigation and proper remediation of such problems [43], it is important to minimize the related negative psychosocial consequences. In addition, special attention should be given to open, respectful, and regular organizational communication [44].…”
Section: Discussionmentioning
confidence: 99%